Resultados exergoeconômicos e exergoambientais de planta de potência integrada a torre solar e heliostatos - Azevedo, Jonathan Leandro Brando de (2019)
The growing demand for power generation makes the search for more efficient ways to produce electricity, with lower costs and lower environmental impacts, be frequent among the research lines. This work analyzed a power conversion cycle using solar energy captured by heliostats and solar tower receiver. The thermal energy storage system has been sized to maintain electricity generation 24 hours a day and compared to the same cycle operating 12 hours a day. The simulation uses the normal direct radiation parameter in Natal-RN to study the cycle behavior in the region. The mathematical model was developed in the EES software and used the SPECO methodology. The cycle components were evaluated according to exergetic, exergoeconomic and exergoenvironmental analysis. The solar system was responsible for the highest rates of exergy destruction and worst exergy efficiency. The results indicate that keeping the cycle running longer hours reduces cycle power and efficiency while the cost and environmental impact of electricity increases. The specific cost of electricity ranged from 48.61 US$/GJ to 85.80 US$/GJ for 12 h and 24 h operation, respectively. Compared to other cycles, the environmental impact of electricity obtained in this work was the lowest: 0.54 mPt/kWh and 0.95 mPt/kWh for 12 h and 24 h operation, respectively. The exergoeconomic approach pointed out the critical components from the economic point of view, while the exergoenvironmental assessment indicated the critical components from the environmental point of view.